PENGARUH PENGGUNAAN SOFTWARE GEOGEBRA TERHADAP PEMAHAMAN KONSEP PADA MATERI TEOREMA PYTHAGORAS - Wahyu, Kristina; Syarifah Fadillah Al Hadad; Nurmaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research uses experimental methods. With the true experimental design research form. The population of this research wa SETIA Pontianak Christian Theology Middle School and the research sample was clas VIII. In this study, 2 classes were taken, namely the experimental class and the control class. The aim of the research is to determine the understanding of concepts before and after being given treatment as well as the influence and differences between those who use geogebra software and those who do not use geogebra software and the differences between the experimental class and the control class in terms of gender. The data collection tool used is a test based on pretest and posttest results. Based on the calculations that have been carried out, the results obtained from understanding the concept before and after being treated with the average pretest and posttest for experimental class increasing significantly, as well as the pretest and posttest for the control class. Meanwhile, the standard deviation of the pretest and posttest for the experimental class increased. Meanwhile, the pretest and posttest of the control class decreased. Then there is an influence betwee the experimental classes. However, there is no difference between classes that use geogebra software and classes that do not use geogebra software. Meanwhil, the results of the differences between the experimental class and the control class in terms of gender are that there is no difference in understanding consepts for learning that uses geogebra software and learning that does not use geogebra software in terms of gender.